Laying the Foundation for Successful School Leadership - Burkhauser, Susan (RAND Corporation, 2013)
RAND researchers provide guidance to state and district decisionmakers, focusing on four areas that research has identified as particularly influential in supporting principal effectiveness: placement in the school, evaluation, autonomy, and resources. We highlight how actions in these areas can create conditions in the school and district that foster principal success.